In the beginning : biblical sparks for a child's week - Hankin, Vered; Kaplan, Kalman J.; Raviv, Amiram (Emerald Publishing Limited : Information Age Publishing, Inc., 2013)
For religious and non-religious alike, the Bible constitutes an important source of cultural heritage, fundamental values, and basic codes of social conduct. This book presents seven Biblical stories ordered to the days of Creation and adapted for children in pre K-5th grades. Day 1: David and Goliath; Day 2: The Tower of Babel; Day 3 Noah and the Flood; Day 4: Abraham Breaking the Idols; Day 5: Jonah and the Big Fish; Day 6: Adam Names the Animals; and Day 7 (The Sabbath): Elijah Rests. Commentaries, questions and activities follow each story and can be used by grandparents, parents and educators to discuss real-life issues with children and foster social skills and values.